Study of Transport Properties of Mineral Chalcopyrite (CuFeS ) at Relatively Low Temperatures (77-300 K): Transport Properties of Mineral Chalcopyrite - Rizvi, Syed Dabir Hasan; Rizvi, Shabana; Raza Naqvi, Syed Munir Mehdi; Raza, Syed Mohsin; Kamaluddin, Shaikh (Biological Sciences - PJSIR, 2010)
The electrical resistivity and thermoelectric power measurements were carried out on chalcopyrite; the mineral rock sample of Balochistan, Pakistan, in a temperature range down from liquid nitrogen temperature up to room tempera- ture (77-300 K). The resistivity studies show diverse transitions at different temperature intervals especially a semi- superconductivity, where weak fermions (not the Cooper pairs) are produced. This transition is accompanied with another relatively low temperature transition, i.e., a metal-insulator transition which sets in at 92 K. The metal to insulator transition at 92 K occurs due to breakup of weak fermions. The Grüneisen function shows a transition at 215 K, where some kind of phonons become free from their respective Brillouin zones. Thus chalcopyrite at 215 K can produce excited phonons for semiconductor, imaging, nanotube, quantum well, optoelectronic and other devices. The sudden escalation of positive thermoelectric power at 240 K in chalcopyrite shows a phase transition perhaps due to diffusional recovery processes, i.e., shuffling of electrons and positive ion cores. Thermoelectric power measured shows an increasing trend similar to that of the theoretically estimated values with a room temperature value around 600 mV/K.